SYNERGY BETWEEN THE YOUTH AND A SECURED NATION: AN ATTEMPT TO DEVELOP NIGERIA THROUGH POLITICS AND ELECTORAL REMINISCENCE - ABDULKAREEM ONAKOYA (International Studies Journal)
Insecurity is another factor battling the political development of Nigeria. It has been observed over the years that no amount of political awareness of the populace, the country will remain underdeveloped politically until this issue is resolved. However, the youths have a lot of roles to play in order to restore the thrust in the government through their participation in the political process and combating with all their strengths the insecurity of the nation. The study therefore aims at examining these roles and some of the impacts of the persistent insecurity on political development in the country. Survey research method with the use of questionnaire to garner responses from various stakeholders and politicians was adopted by the researcher. System Theory was used to navigate the study with expected findings. The result of findings of the study shows that the youths can participate actively in the political affairs of the nation by; joining political parties of their choice, shunning all political violence, engaging in peaceful political rallies and campaigns and ultimately vying for elective positions in the country. It also identifies political apathy, low turnout of voters during elections, disinterest in politics, lack of trust in the leadership and fear of death and intimidation as some impacts of insecurity on political participation of the youths in Nigeria.  The study thereby recommends that; godliness, provision of employment opportunities by the government, secured borders, good parental care etc will improve on the security state of the nation.